Highly porous starch/poly(ethylene-alt-maleic anhydride) composite nanofiber mesh - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2013)
In this study, starch-based hybrid electrospun nanofiber meshes were fabricated by electrospinning. Spinning solutions were prepared by mixing starch and certain amounts of poly(ethylene-alt-maleic anhydride). Starch-based nanofiber meshes became insoluble in water with thermal-induced esterification of hydroxyl groups onto starch backbone. Morphologic and structure analysis of the electrospun nanofiber meshes were investigated by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) techniques. Thermal properties of nanofiber meshes were characterized by thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). Thermal stability of nanofiber meshes were increased with formation of intermolecular bonds between starch and poly(ethylene-alt-maleic anhydride). POLYM. COMPOS. 34:1321-1324, 2013. (c) 2013 Society of Plastics Engineers
Keywords: POLYMER